Defining students’ active participation in a group discussion session from different perspectives - Alias, Masek; Affero, Ismail; Suhaizal, Hashim; Salsabella, Mohd Fizol (2021)
This study was conducted to determine the students’ active participation and validate the students’ learning domains during group discussion sessions. A survey study questionnaire was deployed, including nine constructs to gauge the students’ active participation. The subjects involved 201 randomly selected engineering education students from several polytechnics in the northern region of Malaysia. The students engaged in arguing and cooperating activities, and appeared very enthusiastic during the sessions, and participation was not confined to a particular gender. The implication of the study is that a good facilitating teacher should take into account the nine constructs of the students’ active participation.